2018
DOI: 10.1159/000487319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Colposcopy with Dynamic Spectral Imaging During Routine Practice at Five Colposcopy Clinics in Wales: Clinical Performance

Abstract: Background: The diagnostic accuracy of colposcopy is poor for detecting precancerous cervical lesions. Objectives: We assessed the performance of colposcopy for identifying cervical intraepithelial neoplasia grade 2 or worse (CIN2+), before and after including a dynamic spectral imaging (DSI) map that quantifies and maps acetowhitening to assist subsequent biopsy of suspicious lesions. Methods: Four hundred and twenty-five women were examined at a multi-center setting in Wales, of which 393 women were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…These studies reported an increased sensitivity in using DSI from approximately 50% to about 80-85%. 8,12,13,15 However, there is great inter-observer variation 2,3 in the interpretation of the degree of cervical dysplasia between colposcopist, and also poor correlation between colposcopic impression and biopsy histology. 24 Therefore we believe that our approach of comparing the worst histological…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies reported an increased sensitivity in using DSI from approximately 50% to about 80-85%. 8,12,13,15 However, there is great inter-observer variation 2,3 in the interpretation of the degree of cervical dysplasia between colposcopist, and also poor correlation between colposcopic impression and biopsy histology. 24 Therefore we believe that our approach of comparing the worst histological…”
Section: Discussionmentioning
confidence: 99%
“…New colposcopy technology is now available and has been suggested to improve the performance of colposcopy. [8][9][10][11][12][13][14][15][16] Dynamic spectral imaging (DSI) digital colposcopy measures the aceto-white changes that may occur after application of acetic acid and suggests sites for biopsy through a color coded map. This new technology may be able to increase the sensitivity of colposcopy from 55% to 86%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DSI mapping system (C-DSI) enhances the sensitivity for HSIL/CIN2+ detection, raising it to 86% compared to CC sensitivity [8]. The DSI color-coded mapping system could become an objective tool to assess and select the best sites for biopsy, thus reducing interobserver variability.…”
Section: Introductionmentioning
confidence: 99%
“…Time and resources may be wasted as a consequence in attempting to improve colposcopic diagnostic performance. Furthermore, the colposcopic identification of HSIL from within the group of women referred with low grade squamous intraepithelial lesion (LSIL) cytology is often difficult with a poor sensitivity in part due to low prevalence of pre-cancerous disease in this group [2]. A Eurogin Roadmap examining triage strategies has stressed the importance of a clear triage strategy of each national screening programme either as a single or as a combination option.…”
Section: Introductionmentioning
confidence: 99%